Development and Validation of a Prognostic Nomogram for Extremity Soft Tissue Leiomyosarcoma - Xue, MingFeng; Chen, Gang; Dai, JiaPing; Hu, JunYu (Frontiers in Oncology, 2019)
Background: Extremity soft tissue leiomyosarcoma (LMS) is a rare disease with a poor prognosis. The aim of this study was to develop a nomogram to predict the overall survival (OS) and cancer-specific survival (CSS) of patients with extremity soft tissue LMS. Methods: Based on the Surveillance, Epidemiology, and End Results (SEER) database, 1528 cases of extremity soft tissue LMS diagnosed between 1983 and 2015 were included. Cox proportional hazards regression modeling was used to analyze prognosis and obtain independent predictors. The independent predictors were integrated to develop nomograms predicting 5- and 10-year OS and CSS. Nomogram performance was evaluated by a concordance index (C-index) and calibration plots using R software version 3.5.0. Results: Multivariate analysis revealed that age ≥60 years, high tumor grade, distant metastasis, tumor size ≥ 5 cm, and lack of surgery were significantly associated with decreased OS and CSS. These five predictors were used to construct nomograms for predicting 5- and 10-year OS and CSS. Internal and external calibration plots for the probability of 5- and 10-year OS and CSS showed excellent agreement between nomogram prediction and observed outcomes. The C-index values for internal validation of OS and CSS prediction were 0.776 (95% CI, 0.752–0.801) and 0.835 (95% CI, 0.810–0.860), respectively, whereas those for external validation were 0.748 (95% CI, 0.721–0.775) and 0.814 (95% CI, 0.785–0.843), respectively. Conclusions: The proposed nomogram is a reliable and robust tool for accurate prognostic prediction in patients with extremity soft tissue LMS.